PENYULUHAN KETERAMPILAN KESIAPAN KERJA BAGI MAHASISWA STKIP SINGKAWANG DALAM MENGHADAPI TANTANGAN ABAD-21 - Muliyani, Riski; Kurniawan, Yudi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
This program which was held in the form as instruction of work readiness skills in order to provide the prospective teachers who are able to compete in the globalization era of the work-world in the 21st century. The method of this program that was held at STKIP Singkawang campus is in the instruction about broader skills that intersect with readiness in the world of work. The results of this program indicate that there is an increasing of student’s understanding their self-skill such as broader skills for students if they later complete their education in higher education. In general, this activity went well and smoothly so that it was able to provide benefits to the participants as evidenced by the results of the questionnaire. The follow-up of this program is to prepare regulations or learning strategic in universities so that they are able to provide students with provisions for skills in the world of work in the future